A study on the effects of inner exploration art therapy on the self-recovery function in middle-aged women - Jeong, Yeon-woo; Lee, Myung-sun (Edelweiss Applied Science and Technology, 2025)
Middle-aged women often experience conflicts and confusion in fulfilling roles such as marriage, childbirth, parenting, household chores, and economic activities. These challenges can lead to a lack of self-fulfillment and identity, resulting in physical and mental crises. This study aims to implement an introspective art therapy program to enhance the self-recovery abilities of middle-aged women. To evaluate the program’s effectiveness, self-esteem scales, self-efficacy scales, and the Person Picking an Apple from a Tree (PPAT) projective drawing test were conducted before and after the program and collected data were analyzed for comparison. Participants’ verbal expressions and interactions were examined to visually assess internal changes. The program was designed with four key goals: "self-exploration," "self-understanding," "self-acceptance," and "self-growth," and consisted of 14 sessions. The program’s effectiveness was assessed through quantitative analysis of self-esteem and self-efficacy data, as well as content and formal analyses of PPAT results. Behavioral changes and emotional expressions were qualitatively analyzed using observation records, artwork progress, and photographs. The results demonstrated that introspective art therapy positively influenced self-recovery by promoting self-understanding, exploration, acceptance, and growth. Participants developed positive self-images and values, contributing to improved self-esteem and efficacy. It is implied that the program is effective in enhancing middle-aged women’s ability to recover their sense of self and address challenges positively.